Use of oral moist tobacco (snus) in puberty and its association with asthma in the population-based RHINESSA study - Torben Sigsgaard; Vivi Schlünssen; Mathias Holm; Cecilie Svanes; Christer Janson; Simone Accordini; Andrei Malinovschi; Anna Oudin; Randi Jacobsen Bertelsen; Francisco Javier Callejas; Nils Oskar Jõgi; Juan Pablo López-Cervantes; et al. (BMJ Open Respiratory Research, 2024)
Objectives To investigate the association of early snus use initiation (≤15 years of age) with asthma and asthma symptoms.Design Cross-sectional analysis of a population-based cohort.Setting Study centres in Norway, Sweden, Iceland, Denmark and Estonia, from 2016 to 2019.Participants 9002 male and female participants above 15 years of age of the Respiratory Health in Northern Europe, Spain and Australia study.Main outcome measures Current asthma and asthma symptoms.Results The median age of study participants was 28 years (range 15–53) and 58% were women. 20% had used snus, 29% men and 14% women. Overall, 26% of males and 14% of females using snus started ≤15 years of age. Early snus use initiation was associated with having three or more asthma symptoms (OR 2.70; 95% CI 1.46 to 5.00) and a higher asthma symptom score (β-coefficient (β) 0.35; 95% CI 0.07 to 0.63) in women. These associations were weak in men (OR 1.23; 95% CI 0.78 to 1.94; β 0.16; 95% CI −0.06 to 0.38, respectively). There was evidence for an association of early snus initiation with current asthma (OR 1.72; 95% CI 0.88 to 3.37 in women; OR 1.31; 95% CI 0.84 to 2.06 in men). A sensitivity analysis among participants without smoking history showed stronger estimates for all three outcomes, in both men and women, statistically significant for three or more asthma symptoms in women (OR 3.28; 95% CI 1.18 to 9.10). Finally, no consistent associations with asthma outcomes were found for starting snus after age 15 years.Conclusions Snus initiation in puberty was associated with higher likelihood of asthma and asthma symptoms, with the highest estimates in females and those without smoking history. These results raise concerns about the health adversities of early snus initiation and emphasise the need for public health initiatives to protect young people from this tobacco product.